A Compact Wideband Dielectric Loaded H-plane Sectoral Ridged SIW Horn Antenna - Reshadatmand, M.; Hassani, H. R.; Mohammad Ali Nezhad, S. (Advanced Electromagnetics, 2020)
In this paper a compact and wideband ridged substrate integrated waveguide (RSIW) horn antenna is proposed. Unlike the previous works, the ridge structure in the proposed antenna is tapered only along the width allowing the antenna to be designed on just two-layer dielectric substrate. The tapered ridge is created by simple, different diameter size vias just in one layer. The antenna designed has dimension of 14 × 33 × 3 mm3 (1.4λo × 3.3λo × 0.3λo, where λo is the free space wavelength at 30 GHz) and a has a bandwidth of 41.32% covering 24 - 36.5 GHz with the reflection coefficient, S11, under -10 dB. The antenna is simulated through two software packages CST and HFSS and results are compared.